Pulmonary Mucus Gland Adenomas: Are They Always of Endobronchial Localization? - Georgia Karpathiou; Efthimios Sivridis; Dimitrios Mikroulis; Marios Froudarakis; Alexandra Giatromanolaki (Hindawi Limited, 2013)
Mucus gland adenoma is an extremely rare benign lung tumor, presumed to arise from the bronchial mucus glands; it is a TTF-1 negative tumor, centrally located, causing the clinical manifestations of obstruction. We report a TTF-1 negative mucus gland adenoma, arising into the medial bronchopulmonary segment, lacking any relation to a bronchus.